Single-loop translational space-parallel mechanism with motion decoupling: topological design and kinematics dimension optimization - PAN Haiyue; SHEN Huiping; DU Zhongqiu; LI Tao; LI Ju (Jixie chuandong)
ObjectiveIn response to the issues such as insufficient configuration innovation and incomplete kinematic performance analysis in existing 2-degree-of-freedom parallel mechanisms, the topological synthesis and kinematic performance studies on the novel single-loop translational parallel mechanisms were conducted, aiming to provide fundamental motion unit design theories for link-type modular robots.MethodsFirstly, according to the topology design methodology of the parallel mechanism (PM) based on position and orientation characterization (POC), four single-loop translational spatial PMs consisting of two prismatic joints and five rotating joints were proposed, and their topological analysis was performed. Secondly, the symbolic positional positive and negative solutions, workspaces, and the singularities and their singular positions were derived for each of the four PMs and verified, respectively. Finally, the differential evolution algorithm was used to optimize the maximum workspace of the four mechanisms, and their maximum workspace were finally obtained.ResultsThis single-loop translation spatial parallel mechanism can be used to design the unit of modular rod-type robots. This work lays a foundation for the design and its stiffness, kinematic error, dynamics analysis of the modular robot based on this unit.